Enhancing Customer Delight in LED Televisions by Using the KANO Model - Saranya, K.; Santhi, P. (Indian Journal of Marketing, 2016)
Customer requirement management has become one of the principal factors for product development to succeed in the market place. Product is the most important element in the marketing mix. It provides the functional requirements sought by customers. The television market in India is graduating from the cathode ray (CRT) television to LED (light emitting diode) television. The technology applied television creates new needs even as they serve others. The Kano model is a better tool for determination of customer requirements for new product development and innovation. The Kano model has been applied for multiple new product design and innovation for compliance with customer needs with respect to customer satisfaction. The objective of the present study was to measure product requirements from customers’ perspectives for product development and thereby to achieve a competitive advantage in the LED television market. The study was based on primary data collected from 150 sample respondents (drawn by using the random sampling method) who were the users of LED television, irrespective of the brand of television. The positive customer satisfaction coefficient on the feature : clear motion rate brought more than proportional satisfaction. The quality improvement index brought out the key product features that could be incorporated in designing LED television to gain a competitive advantage in the LED television market.